2011
DOI: 10.1242/jcs.082644
|View full text |Cite
|
Sign up to set email alerts
|

IGF binding protein 3 exerts its ligand-independent action by antagonizing BMP in zebrafish embryos

Abstract: SummaryIGFBP3 is a multi-functional protein that has IGF-dependent and IGF-independent actions in cultured cells. Here we show that the IGF binding domain (IBD), nuclear localization signal (NLS) and transactivation domain (TA) are conserved and functional in zebrafish Igfbp3. The in vivo roles of these domains were investigated by expression of Igfbp3 and its mutants in zebrafish embryos. Igfbp3, and its NLS and TA mutants had equally strong dorsalizing effects. Human IGFBP3 had similar dorsalizing effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Martin et al 2009;Naspi, et 353 al. 2017;Zhong, et al 2011). In many situations, IGFBP-3 was a tumour suppressor, but it may also 354 have pro-tumourigenic actions; modulation of sphingolipids was proposed to underlie these 355 apparently opposing effects (Baxter 2014).…”
Section: Igf-independent Actions 342mentioning
confidence: 99%
“…Martin et al 2009;Naspi, et 353 al. 2017;Zhong, et al 2011). In many situations, IGFBP-3 was a tumour suppressor, but it may also 354 have pro-tumourigenic actions; modulation of sphingolipids was proposed to underlie these 355 apparently opposing effects (Baxter 2014).…”
Section: Igf-independent Actions 342mentioning
confidence: 99%
“…Previous studies on the biology of Igfbps in fish have shown that Igfbps regulate embryonic development (Duan et al 1999, Kajimura et al 2005) and exert ligand-dependent and -independent mechanisms (Dai et al 2010, Zhong et al 2011, as well as showing that Igfbps are modulated by Gh treatment (Duan et al 1999, Cheng et al 2002, Chen et al 2004, Pedroso et al 2009b, oxygen availability (Kajimura et al 2005, Rahman & Thomas 2011, Sun et al 2011, reproduction , Chen et al 2010, and nutrition , Bower et al 2008, Pedroso et al 2009a, Peterson & Waldbieser 2009, Amaral & Johnston 2011, Macqueen et al 2011. Nevertheless, studies on local muscle-derived igfbps (autocrine/ paracrine) have been scarce and have recently shown contrasting results, reflecting a complex physiology of Igfbps and suggesting that intricate patterns of regulation have evolved between and within teleost lineages , Bower et al 2008, Amaral & Johnston 2011, Macqueen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Broadening of the axial mesoderm has previously been observed in zebrafish upon Igfbp-3 overexpression (Zhong et al, 2011), indicating that Papp-a2 might modulate BMP signaling by proteolytic cleavage of Igfbp-3. In accordance with such mechanism, human IGFBP-3 was recently reported to bind BMP2 and BMP4 thereby antagonizing their signaling activity Zhong et al, 2011). Furthermore, zebrafish Bmp1 cleaves Igfbp-3, and proteolytic cleavage of human IGFBP-3 by BMP1 is known to reduce its affinity for BMP4 .…”
Section: Discussionmentioning
confidence: 74%
“…In addition, broadening of the noto-expression domain has been reported in zebrafish embryos overexpressing igfbp-3 (Zhong et al, 2011), indicating a functional link between Pappa2 and Igfbp-3. For biochemical characterization, we transfected HEK293T cells with zebrafish papp-a2 cDNA and confirmed its expression by western blotting (Fig.…”
Section: Expression Analysismentioning
confidence: 96%